Analisis Literatur Review Perencanaan Strategi Sistem Informasi Menggunakan Metode Metode Five Competitive Force Pada CV. Bio Chitosan Indonesia - Susan Juli Safitri; Gelar Alam Ramdhaniawan; Asro Asro; Novi Rukhviyanti (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The rapid development of science and technology, in line with the progress of time, has led to the increased use of personal computers, playing a crucial role in assisting human tasks. Additionally, the use of technology in work processes helps to improve speed and accuracy compared to not using technology. Today, Systems Information and Technology (SI/IT) are not only needed as tools to support an organization's operational activities but also as an essential aspect of business strategy to achieve organizational goals. Computer-based information systems have now become a primary necessity for fulfilling information needs. Many sectors have utilized computer information systems as a means to simplify tasks. Therefore, this journal will discuss